Leveraging technology to increase the disseminability of evidence‐based treatment of dental fear: An uncontrolled pilot study - Heyman, Richard E.; Daly, Kelly A.; Slep, Amy M. Smith; Wolff, Mark S. (Journal of public health dentistry, 2024)
Objectives U.S. and global estimates indicate that over 30% of adults fear receiving dental care, including over 20% who have visited a dentist in the last year, leading to avoidance and degraded oral and systemic health. Although evidence‐based cognitive‐behavioral treatments for dental fear (CBT‐DF) exist, they have little impact on the millions who seek dental care annually because they are not disseminable (6 h of in‐chair time, delivered only in person at a few sites). We developed a disseminable CBT‐DF stepped‐care treatment comprising (Step 1) a mobile‐health application and, for those who remain fearful, (Step 2) a 1‐h, one‐on‐one psychological treatment session that allows practice during exposure to the patient's most‐feared stimuli. We hypothesized that the treatment would (a) be rated highly on usability and credibility and (b) result in clinically consequential (i.e., lowering fear into the 0–3 “no/low fear” zone) and statistically significant changes in global dental fear. Method Racially/ethnically diverse patients (N = 48) with moderate to severe dental fear were recruited; all completed Step 1, and n = 16 completed Step 2. Results As hypothesized, users found the stepped‐care treatment highly usable, credible, and helpful. Critically, this stepped‐care approach produced reductions in patients' dental fear that were both clinically consequential (with half no longer fearful) and statistically significant (d = 1.11). Conclusions This usable, credible, stepped‐care approach to dental fear treatment holds promise for liberating evidence‐based CBT‐DF from specialty clinics, allowing broad dissemination.